Land degradation in Mhondoro (Zimbabwe) : an environmental assessment of communal land uses and resource management practice - Tichagwa, Cornelius Gibson (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2002.